2021
DOI: 10.2147/copd.s311659
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Luminal Mucus Score in Large Airways with Lung Function and Quality of Life in Severe Acute Exacerbation of COPD: A Cross-Sectional Study

Abstract: Background and Objective Luminal mucus plugging in small airways is associated with lung function decline and death of patients with chronic obstructive pulmonary disease (COPD). However, little attention has been paid to the possible role of mucus in large airways in acute exacerbation of COPD (AECOPD). Therefore, this study aimed to explore the relationship between the luminal mucus score of large airways and other physiological parameters of severe AECOPD. Subjects and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…One potential consequence of aberrant MCC in conducting airway is retention of inhaled substances (micro-organisms, cigarette smoke, air pollutants, etc. ), leading to chronic inflammation in alveolar regions and worse health-related quality of life (Yang et al, 2021). Alternatively, overexpression of mucus or hyperplasia of mucus-producing cells in the conducting airway may also promote the mucous aspirated into the distal airway and thus leading to gas exchange impairment (Leitz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One potential consequence of aberrant MCC in conducting airway is retention of inhaled substances (micro-organisms, cigarette smoke, air pollutants, etc. ), leading to chronic inflammation in alveolar regions and worse health-related quality of life (Yang et al, 2021). Alternatively, overexpression of mucus or hyperplasia of mucus-producing cells in the conducting airway may also promote the mucous aspirated into the distal airway and thus leading to gas exchange impairment (Leitz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 prospective study found substantial correlations between secretion volume, colour, mucosal oedema, and erythema, with BAL neutrophils indicating the level of airway inflammation [ 10 ]. While the BS is primarily used in assessing asthma and chronic obstructive pulmonary disease [ 22 , 23 ], its application in the quantitative assessment of pulmonary conditions in infectious pneumonia is less common [ 8 , 24 ]. Hence, this endoscopic scoring standard requires further validation through extensive studies, and there is a paucity of reports on the severity of MP assessed through bronchoscopy for endobronchial changes.…”
Section: Discussionmentioning
confidence: 99%
“…etc. ), which initiates chronic inflammation in alveolar regions and reduces lung functions (52). Also, mucus accumulation may promote mucus aspiration into distal airways, impairing the gas exchange process (53).…”
Section: Discussionmentioning
confidence: 99%